Comparison of a new immunoassay and PCR-based method for quantification of microRNAs in whole blood. A pilot methodical study - Stejskal, David; Hlozankova, Martina; Sigutova, Radka; Andelova, Katerina; Svagera, Zdenek; Svestak, Marek (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2019)
BACKGROUND: MicroRNAs (miRNAs) are new generation biomarkers used in oncology, cardiology, metabolic syndrome, obesity or in neurology. miRNAs are short non-coding RNA molecules that regulate gene expression in eukaryotes. AIM: To compare a new commercial method for establishing miRNA (imunoassay) with a commercial kit RT qPCR. METHODS: RNA was isolated from whole blood samples obtained from four healthy volunteers. The isolates were liquated and miRNA-93-5p and miRNA-23a-3p were measured independently with commercial hsa-miR-93-5p miREIA and hsa-miR-23a-3p miREIA, and commercial RT-qPCR kits. RESULTS: Both miRNAs had good analytical characteristics, very good correlation with RT qPCR. The results between immunoassay and RT qPCR did not statistically differ. A method based on ELISA was faster (2 h with ELISA vs. 3 h with qPCR) and had lower CV then a method based on RT qPCR (see more text). CONCLUSION: MicroRNAs from blood or derived fractions are particularly interesting candidates for routine laboratory applications. The immunoassay can be performed on any device that processes the ELISA plates and is therefore available in almost every laboratory.
Keywords: MicroRNAs; biologické markery; kvantitativní polymerázová řetězová reakce; Reagent Kits, Diagnostic; Biomarkers; mikro RNA; pilotní projekty; immunoassay; stanovení celkové genové exprese; Real-Time Polymerase Chain Reaction; reprodukovatelnost výsledků; ELISA; Reproducibility of Results; Gene Expression Profiling; PCR; Enzyme-Linked Immunosorbent Assay; lidé; Humans; microRNA; zdraví dobrovolníci pro lékařské studie; Pilot Projects; reagenční diagnostické soupravy; Healthy Volunteers